The infrastructure and equipment in the practice of competitive sport for athletes of combat Leagues in Nariño, Colombia - Claudia Patricia Castaño Herrera; Mario Acevedo Ruisanchez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2017)
The article talks about the resources of sub category of the final report called Psychosocial and Sports conditions for Athletes in Combat Leagues in the Department of Nariño. Above mentioned article aimed to characterize the sport conditions as the training environment of these athletes in relation of the Infrastructure and Equipment. The study board under the qualitative paradigm, used focus group interviews and observation of participant showing results and discussion of combat sports that require an exchange of efforts and explosiveness in the training area. Therefore it is needed high level of comfort in infrastructure, typology, technical conditions of sport, hygiene, accessibility to quality materials.  Otherwise, it would place the athletes at risk when they participate in national or international competitions because they do not have a real workout and it will negatively impacting their performance. Likewise the equipment and clothing that is used for training is not the same as used in competitions, which can causing them risks and injuries that threaten their health and integrity. Moreover, it is seen from their expressions that there is a need for greater concern and planning into the management and organization and investments to quality of sports services of the organizations, city halls and the Government of Nariño. That fact should be improved to ensure quality conditions that require athletes of high level competition.